Factors That Impact Impulsive Buying in Offline Beauty Stores in Indonesia - Naja Ghassani Widyaputri; Atik Aprianingsih (Mandalika Journal of Business and Management Studies, 2024)
The COVID-19 pandemic significantly impacted the retail industry, especially beauty retail stores, as consumer behavior shifted drastically. With the temporary closure of physical stores and a surge in e-commerce, offline beauty stores saw a substantial drop in sales. As the world transitions to the post-pandemic era, beauty retailers need new strategies to boost in-store sales. Impulse buying behavior is one potential strategy which has been identified as a significant driver of retail sales in offline beauty stores. Therefore, this research aims to analyze the key factors influencing impulse purchases at offline beauty stores in Indonesia and also analyze which variables can positively influence impulse purchases at offline beauty stores in Indonesia. This research used quantitative research using questionnaires with non-probability and purposive sampling is used, so the respondents must have purchased at least once purchased in offline beauty stores, be 18-65 years old, and living in Indonesia. Using a survey method with 250 respondents, data were analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that sales promotions, store environment, and store employees significantly impact impulse buying behavior. These findings can help beauty retail business or similar businesses in the beauty industry in developing strategies to enhance customer experience and increase in-store sales by leveraging the identified influential factors.